Estilo de vida de agentes comunitários de saúde: uma associação com a qualidade de vida e saúde mental - FANAN, Júlia Maria Vergani (2019)
The aim of this study was to evaluate the association of lifestyle based on 8 health promotion practices with quality of life and mental health of Community Health Agents (ACS). Cross-sectional study conducted with 78 CHA from a health district in a city in the interior of Minas Gerais through questionnaires that assessed Lifestyle (Questionnaire 8 Natural Remedies - Q8RN), Quality of Life (WHOQOL-Bref) and Health Self-Reporting Questionaire 20 - SRQ-20). For associations between lifestyle and quality of life, multiple linear regression was performed and for association between lifestyle and mental health, Poisson regression was performed, adopting p values <0.05 and confidence interval (CI) of 95%. %. Most participants were female (97.4%), with a mean age of 40.1 years, living with a partner (69.2%), complete high school (73.1%) and income of 1 to 3 minimum wages (61.5%). An average of 3.64 diseases and 1.47 medications per participant were identified. Regarding Lifestyle, participants were classified according to Q8RN into “Very Good / Excellent” lifestyles (9%); “Good” (46.2%); “Insufficient / Regular” (44.9%). It was observed that a “Very Good / Excellent” lifestyle was associated with higher scores in all quality of life domains. In associating lifestyle with mental health, participants who rated their lifestyle as “Very Good / Excellent” were more likely to have no mental distress when compared to those who rated “Insufficient / Regular”. We highlight the positive association of lifestyle based on 8 health promotion practices (model adopted in this study), with quality of life and mental health, highlighting the importance of such practices for the quality of life and mental health of ACS and, consequently, their assistance to the population.